Republic of Korea : Financial Sector Assessment Program-Technical Note-Financial Conglomerates Supervisions. (IMF Staff Country Reports; Country Report ;, 2020)
Oversight of the Korean financial system is broadly effective. Korea's Financial Services Commission (FSC) and Financial Supervisory Service (FSS) have in place regulatory and supervisory regimes in line with international standards with only a few remaining gaps. The authorities have addressed most of the recommendations of the previous FSAP and made good progress in benchmarking their frameworks with the Basel Core Principles (BCP), the Insurance Core Principles (ICP) and the International Organization of Securities Commissions (IOSCO) Objectives and Principles for Securities Supervision (IOP).